2019
DOI: 10.1177/1742271x19853859
|View full text |Cite
|
Sign up to set email alerts
|

Echo intensity reliability between two rectus femoris probe sites

Abstract: Introduction The ultrasound technique has been extensively used to measure echo intensity, with the goal of measuring muscle quality, muscle damage, or to detect neuromuscular disorders. However, it is not clear how reliable the technique is when comparing different days, raters, and analysts, or if the reliability is affected by the muscle site where the image is obtained from. The goal of this study was to compare the intra-rater, inter-rater, and inter-analyst reliability of ultrasound measurements obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
3
7
1
Order By: Relevance
“…We are not aware of any other studies that have examined the effect of the rater's level of experience in acquiring LMM EI measurements. However, our findings are in accordance with other studies that have examined EI measures in other muscle groups [56][57][58].…”
Section: Inter-rater Reliabilitysupporting
confidence: 93%
See 2 more Smart Citations
“…We are not aware of any other studies that have examined the effect of the rater's level of experience in acquiring LMM EI measurements. However, our findings are in accordance with other studies that have examined EI measures in other muscle groups [56][57][58].…”
Section: Inter-rater Reliabilitysupporting
confidence: 93%
“…The authors reported an inter-rater ICC of 0.897 and 0.837 for the abductor pollicis brevis and abductor digiti minimi muscle, respectively. Accordingly, it appears that even with minimal experience or training by the rater, the reliability of EI muscle measurements are good to excellent [56][57][58]. These findings are similar to our study, which showed good to excellent reliability between the novice raters and the experienced rater, except for Novice 1 for the right LMM, which revealed lower ICCs and a wider 95% CI.…”
Section: Inter-rater Reliabilitysupporting
confidence: 89%
See 1 more Smart Citation
“…Importantly, although the direction of change will likely be the same across a range of settings, the magnitude of change will likely be different. Probe sites should also be considered, as measurements from different muscle regions might result in different responses [79]. However, with respect to the impact of exercise, the important question would be "do different regions of the muscle result in different changes?"…”
Section: Mechanical Considerationsmentioning
confidence: 99%
“…This allows for controlling intervening variables and ascertaining whether changes in the participant's results are truly due to an adaptation and not to changes in the US system parameters. Reliability studies have been conducted to quantify the influence of moments, 21,22 raters, 23,24 transducer tilt, 25 muscle site, 24 image analysis technique, 26,27 and analysts 24,28 on the results, finding that reliability of EI measurements are high to very high. However, few studies have evaluated the influence of using different US systems on muscle EI values.…”
mentioning
confidence: 99%